Information signal and medical diagnosis: Audit study evidence from Georgia - Renate Hartwig; Dimitri Japaridze; Nana Khetsuriani; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2024)
Evidence on how digital technologies, such as online health information platforms, affect the doctor-patient relationship in general, and the diagnosis and treatment of patients in particular, is still limited. In this study, we explore the effects of alternative information from an online source on the diagnosis and treatment behavior of doctors in Tbilisi, Georgia. We use data from standardized patient visits and assess quality of care on the basis of case management of diabetes type II - a disease which is on the rise in Georgia. We find that doctors do not respond to the information signal and that case management is unaffected by the information provided. This finding holds across a number of dimensions of clinical case management, including the number of symptoms checked, the number of clinical tests performed, the time spent with the patient and the costs charged for consultations and medical tests.
Keywords: H42; I11; I18; O15; 330; Health Care; Standardized Patient; Diabetes